Analysis of First Professional Written Short-Answer Questions of Four Public Universities of Bangladesh in Regional Anatomy - Yasmin, Farhana; Wahid, Sumaiya Binte; Uzzaman, Md Akter (Mediscope, 2024)
Background: Analysis of written question papers may reveal the assessment pattern and teaching- learning method of the undergraduate curriculum. Written examination is the most essential assessment tool in the MBBS curriculum and the subjective knowledge of the undergraduates’ can be well assessed by the written assessment. Therefore, analyses of written question papers may reveal the assessment pattern and teaching learning method of undergraduate curriculum. The present study has assessed the weightage given to the different components of cognitive domain in SAQs in the First Professional MBBS Examination in Regional Anatomy under four public universities of Bangladesh. Objective: To determine the frequencies of question-segments addressing different levels of cognitive domain in the First Professional MBBS written examination in Regional Anatomy of five years (2014-2018) of four public universities of Bangladesh. Methods: This descriptive type of research was conducted in the Department of Anatomy, BSMMU, Dhaka. Anatomy written short-answer questions (SAQs) both paper I and paper II from 2014 to 2018 of four public universities of Bangladesh were analyzed to determine the frequency of ‘question-segment’s addressing different levels of cognitive domain according to undergraduate medical curriculum. Results: On analysis it was found that 91.42% ‘question-segments’ were remember-level and 8.58% were understand-level. No ‘question-segment’ was found that have addressed apply-, analyze-, evaluate- or create-levels of cognitive domain. Conclusion: The research revealed that higher levels of cognitive domain was not addressed properly in the undergraduate written question papers, so, goals of undergraduate curriculum were poorly achieved. Mediscope 2024;11(2): 52-57